2016
DOI: 10.1007/s00535-016-1232-y
|View full text |Cite
|
Sign up to set email alerts
|

A human gut ecosystem protects against C. difficile disease by targeting TcdA

Abstract: Background A defined Microbial Ecosystem Therapeutic (MET-1, or “RePOOPulate”) derived from the feces of a healthy volunteer can cure recurrent C. difficile infection (rCDI) in humans. The mechanisms of action whereby healthy microbiota protect against rCDI remain unclear. Since C. difficile toxins are largely responsible for the disease pathology of CDI, we hypothesized that MET-1 exerts its protective effects by inhibiting the effects of these toxins on the host. Methods A combination of in vivo (antibioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 66 publications
0
21
0
1
Order By: Relevance
“…Many studies have also demonstrated that Lactobacillus and Bifidobacterium are associated with colonization resistance against C. difficile (Lawley et al, 2012;Petrof et al, 2013;Valdes-Varela et al, 2016;Martz et al, 2017;De Wolfe et al, 2018;Vedantam et al, 2018). Bifidobacterium longum JDM301, a widely used commercial probiotic strain, can inhibit C. difficile growth and degrade TcdA and TcdB, and the author further proved that the exertion of inhibition of B. longum is dependent on an acidic pH (Wei et al, 2018).…”
Section: Introductionmentioning
confidence: 94%
“…Many studies have also demonstrated that Lactobacillus and Bifidobacterium are associated with colonization resistance against C. difficile (Lawley et al, 2012;Petrof et al, 2013;Valdes-Varela et al, 2016;Martz et al, 2017;De Wolfe et al, 2018;Vedantam et al, 2018). Bifidobacterium longum JDM301, a widely used commercial probiotic strain, can inhibit C. difficile growth and degrade TcdA and TcdB, and the author further proved that the exertion of inhibition of B. longum is dependent on an acidic pH (Wei et al, 2018).…”
Section: Introductionmentioning
confidence: 94%
“…With respect to well-established defined communities, the probiotic cocktail VSL#3 and the fecal transplant substitute MET-1 have been tested on various human or animal intestinal cell lines (Caco-2, T84, and HT-29) (e.g., see references [138][139][140]. In most studies, however, the use of bacterial lysates or conditioned media was preferred over live bacteria (e.g., see references 72 and 141-144), because the (mainly anaerobic) gut bacteria cannot survive under the aerobic conditions needed for intestinal cell culture.…”
Section: Modeling the Host In Vitromentioning
confidence: 99%
“…Many pharmaceutical firms are actively working to bring easily consumable CDI-targeted drugs based on FMT. A defined microbial ecosystem therapeutics (MET-1 or RePOOPulate) was developed to cure recurrent CDI [136,137]. The closest enema-based drug that is awaiting clinical approval is RBX2660, which depends upon the microbial suspension provided from the donor and is formulated for therapeutic delivery.…”
Section: In Treating Diseases Associated With Gut Microbiota-associatmentioning
confidence: 99%